Cost and Return in Vanilla Cultivation-A Study with Special Reference to Coimbatore District - Mahalakshmi, K. (Indian Journal of Marketing, 2009)
Agriculture becomes more luring if the returns reaped are higher as compared to the costs involved. Vanilla crop has become a plant of promising returns to the farmers of Coimbatore region, who cultivate Vanilla as an intercrop in their fields with a hope to realise high profit. Since many farmers have taken Vanilla crop cultivation and as many financial agencies are willing to finance Vanilla cultivation, a study on returns through Vanilla cultivation becomes all the more important as the result would be an eye-opener to many concerned-Government, Banks, NGOs, and farmers.